Barchester Towers - Trollope, Anthony, 1815-1882 (Salt Lake City, UT : Project Gutenberg, 2002)
"Barchester Towers" by Anthony Trollope is a novel published in 1857. When the beloved bishop dies, a power struggle erupts in the cathedral city of Barchester. The evangelical Bishop Proudie arrives with his domineering wife and scheming chaplain Mr. Slope, who all clash with the established clergy. Romantic entanglements, social maneuvering, and misunderstandings complicate matters as characters vie for position and love. This satirical portrait of Victorian clerical life explores ambition, marriage, and the collision between old and new religious sensibilities. (This is an automatically generated summary.)
Wikipedia page about this book: https://en.wikipedia.org/wiki/Barchester_Towers
Release date is 2002-09-01
E-text prepared by David J. Cole and revised by Joseph E. Loewenstein, M.D.
Keywords: Barchester (England : Imaginary place) -- Fiction; Domestic fiction; Clergy -- Fiction; Barsetshire (England : Imaginary place) -- Fiction